Repurposing the anthelminthic salicylanilide oxyclozanide against susceptible and clinical resistant Candida albicans strains. (14th May 2018) - Pic, Emilie; Burgain, Anaïs; Sellam, Adnane
Abstract: Current antifungal drugs suffer from limitations including toxicity, adverse interactions with other commonly prescribed drugs, and the emergence of resistant strains. Here, we repurposed the anthelmintic oxyclozanide as a potent antifungal agent against both sensitive and resistant clinical isolates of Candida albicans, as well as other human opportunistic fungi. Antifungal activity of oxyclozanide was enhanced when C. albicans grew in nonfermentable carbon sources. Our data support a mechanism of action where oxyclozanide uncoupled the mitochondrial electron transport from oxidative phosphorylation and perturbed the mitochondrial membrane potential.